Dynamic regulation of serum aryl hydrocarbon receptor agonists in MS - Rothhammer, Veit; Borucki, Davis M.; Sanchez, Maria Isabel Garcia; Mazzola, Maria Antonietta; Hemond, Christopher C.; Regev, Keren; Paul, Anu; Kiviakk, Pia; Bakshi, Rohit; Izquierdo, Guillermo; Weiner, Howard L.; Quintana, Francisco J. (Neurology, Neuroimmunology and Neuroinflammation, 2017)
Objective: Several factors influence the clinical course of autoimmune inflammatory diseases such as MS and inflammatory bowel disease. Only recently, the complex interaction between the gut microbiome, dietary factors, and metabolism has started to be appreciated with regard to its potential to modulate acute and chronic inflammation. One of the molecular sensors that mediates the effects of these environmental signals on the immune response is the aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor with key functions in immune cells. Methods: In this study, we analyzed the levels of AHR agonists in serum samples from patients with MS and healthy controls in a case-control study. Results: We detected a global decrease of circulating AHR agonists in relapsing-remitting MS patients as compared to controls. However, during acute CNS inflammation in clinically isolated syndrome or active MS, we measured increased AHR agonistic activity. Moreover, AHR ligand levels in patients with benign MS with relatively mild clinical impairment despite longstanding disease were unaltered as compared to healthy controls. Conclusions: Collectively, these data suggest that AHR agonists in serum are dynamically modulated during the course of MS. These findings may guide the development of biomarkers to monitor disease activity as well as the design of novel therapeutic interventions for MS.
CRIS-Team Scopus Importer:2020-09-22